- #1

John Delaney

- 3

- 1

- Homework Statement
- Prove εijk εijl = 2δkl

- Relevant Equations
- εijk εilm = δjl δkm - δjm δkl

I assumed that this would be a straightforward proof, as I could just make the substitution l=j and m=l, but upon doing this, I end up with:

δjj δkl - δjl δkj

= δkl - δlk

Clearly I did not take the right approach in this proof and have no clue as to how to proceed.

δjj δkl - δjl δkj

= δkl - δlk

Clearly I did not take the right approach in this proof and have no clue as to how to proceed.